Crystalline and optoelectronic properties of Ge1−xSnx/high-Si-content-SiyGe1−x−ySnx double-quantum wells grown with low-temperature molecular beam epitaxy. (1st January 2023) - Zhang, Shiyu; Shibayama, Shigehisa; Nakatsuka, Osamu
Abstract: In this study, we investigated the impact of the growth temperatures of molecular beam epitaxy method for the Si y Ge1− x − y Sn x barrier with a Si content over 20% of Ge1− x Sn x /Si y Ge1− x − y Sn x single-quantum well (QW) on their crystalline and photoluminescence (PL) properties. As a result, we found that lowering T SiGeSn down to 100 °C achieves the superior crystallinity and the higher PL efficiency at room temperature. It was owing to the suppression of the Sn segregation according to the surface morphology observation. Based on this finding, we realized the epitaxial growth of Ge1− x Sn x /Si y Ge1− x − y Sn x double-QWs at 100 °C. We verified the superior crystallinity with the abrupt interface by x-ray diffraction and scanning transmission electron microscopy. In this study, we discussed the optical transition mechanism of the single- and double-QWs based on the band alignment simulation. Finally, we found that the double-QW grown at 100 °C can sustain its crystalline structure against annealing at the N2 atmosphere up to 350 °C, and the PL performance can be also improved by the thermal treatment at around 350 °C.